Rotational pasture management in beef cattle with emphasis on animal welfare (Research, Society and Development, 2022)
Livestock is currently seen as one of the most profitable activities in rural areas, with the advancement of technology, several improvements have been applied in this environment such as genetic improvement, forage improvement, and intensification in management, to take full advantage of the property and optimize the production time. Based on this, the present work was carried out as a literature review in order to report as a focus the rotational management in beef cattle with an emphasis on animal welfare, approaching pasture systems, describing each pasture system and emphasizing the advantages of rotational pasture management in beef cattle, taking into account several factors that improve and increase production such as the use of the area, which can increase its animal unit per hectare, uniform use of forage, among others, causing the producer to produce a product of quality in the shortest possible time, consequently having a higher annual profit.